Antineoplastic-related cardiovascular toxicity: A systematic review and meta-analysis in Asia. (September 2019) - Leong, Siew Lian; Chaiyakunapruk, Nathorn; Lee, Shaun Wen Huey
Abstract: Background: Cancer and heart diseases are the leading causes of morbidity and mortality in many countries worldwide. Recent advancement in chemotherapy and targeted therapies has led to an improvement in cancer survival rates, but at a cost of higher cardiac side effects. However, report on antineoplastic-related cardiotoxicities incidence in Asia is lacking. Methods: We systematically searched multiple databases to identify studies reporting incidence of antineoplastic-related cardiovascular toxicity in Asia published from inception to November 2018. Pre-specified subgroups were performed to explore heterogeneity and study quality assessed and reported according to PRISMA guidelines. Results: A total of 61 studies across 11 countries in Asia reported 8 types of cardiovascular toxicities were included. These studies mostly reported on adult populations, and usually examined cardiotoxicities related to anthracycline use. The most frequently reported cardiotoxicities were heart failure, electrocardiogram abnormalities and left ventricular dysfunction. The pooled estimated incidence of cardiotoxicity was 4.27% (95% CI: 3.53–5.07). Subgroup analysis showed higher incidence in middle income countries compared to high income countries. Conclusions: Although robust incidence studies are sparse, cardiovascular complications affects approximately one in twenty cancer patients in Asia. This highlights a unique opportunity of cancer patients caring that need cardiologists and oncologist to become familiar with this emerging sub-specialty.